Effects of COVID-19 on Financial Sector and the Role of Social Media as an Advertising Tool: A Case in Zimbabwe - Chirume, Enesiti (Current Aspects in Business, Economics and Finance Vol. 3, 2022)
This study highlights the implications of COVID-19 on the financial sector and looks at how social media is used as an advertising medium in Zimbabwe. The objectives of the study were to identify the effects of COVID-19 on the financial sector in Zimbabwe, and to explore the role of social media as an advertising tool: A Case in in Zimbabwe. Drawing respondents from ten (10) leading financial institutions in Zimbabwe, the study used a self-administered interview schedule and adopted the qualitative research design. Challenges identified ranged from maintaining cash and liquidity to re-adjusting operations (dropping profits and staff well-being). Noted also, were pressures on financial institutions notably, the rise of fin-tech within the sector to serve customer needs. This paper agrees with some scholarly views on what ought to be the additional and new role of social media as an advertising tool- and that is relating social media contributions to the real-time context. For the financial institutions, it is not business as usual. At the time of writing, the length of the crisis and the depth of its severity were still unknown globally. This period presented a rare and unique opportunity for the financial institutions in Zimbabwe to use social media advertising for connecting and bonding with customers in meaningful ways. This involved altering advertising strategies, assessing the language used in advertisements, and realising that consumers were more anxious than usual during the trying situations.